Efektivitas Praperadilan dalam Membatalkan Penetapan Tersangka - Moonti, WIndah; Moonti, Roy Marthen (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Pretrial is an important instrument in the Indonesian criminal justice system that serves as a control mechanism against arbitrary actions of law enforcement officials, especially in the determination of suspect status. This study aims to analyze the effectiveness of pretrial institution in overturning invalid suspect determination and its impact on the protection of human rights and legal certainty. The method used is normative legal research with legislative approach and case study. The results of the study show that although pretrial has been strengthened through Constitutional Court Decision No. 21/PUU-XII/2014, in practice its effectiveness is still limited due to inconsistency of decisions, lack of access to investigation documents, and potential abuse by certain parties. Pre-trial decisions that invalidate suspect determinations have a substantive impact in upholding the principle of presumption of innocence and due process of law. However, in order for it to function optimally, reform of KUHAP, training of judges, digitization of the judicial process, and strong public oversight are required. Thus, pretrial can play a strategic role in maintaining substantive justice and the integrity of the legal system in Indonesia.